Flux Analysis with the Application of Darcy’s Law Based on Borehole Data for Sustainable Groundwater Exploitation - Zul Fadhli; Khaira Khirnica; Muhammad Syukri; Layna Miska; Yurda Marvita; Marwan Marwan; Dian Budi Dharma (School of Postgraduate Studies, Diponegoro Univer, 2025)
The potential for groundwater is very large and widely distributed in Aceh Besar District as indicated by the Groundwater Basin map. This potential is supported by the presence of sedimentary deposits consisting of materials such as gravel, sand and clay. This research was conducted to identify the type of aquifer and calculate the amount of groundwater discharge in the district of Aceh Besar. The discharge calculation is carried out using Darcy's Law where this equation can be used to describe the ability of the aquifer to flow through the rock. This study also compares the results of calculating the water discharge using Darcy's Law with the real Pumping Test data. The results showed that the coastal area of Aceh Besar was dominated by confined aquifers with average depth of 40-120 m and thickness of 3-30 m. The results of calculating the water discharge (flux) in the study area were obtained around 3414.61 m/day or equivalent to 39.51 liters/second. The results of comparison with the real Pumping Tes data in segment 2 found that the results of calculating discharge using Darcy's Law were 23.93 liters/second while the results of real Pumping Test were 25.5 liters/second so that the error value found is 6.1%, and in segment 3 the results of calculating discharge using Darcy's Law is 21.88 liters/second while the results of the real Pumping Test are 21 liters/second so that an error value of 4.2%.. From the results of these two comparisons, it can be seen that the calculation of water discharge using Darcy's Law is comparable and has significant results with the results obtained from the real Pumping Test, so that the calculation of water discharge using Darcy's Law can be used for a reference in the groundwater exploitation.